Avaliação da poatencialidade da perlita natural e expandida na adsorção de metais - Belarmino, Loilde Damasceno (2012)
The contamination by metal ions has been occurring for decades through the introduction of liquid effluent not treated, mainly from industrial activities, rivers and lakes, affecting water quality. For that the effluent can be disposed in water bodies, environmental standards require that they be adequately addressed, so that the concentration of metals does not exceed the limits of standard conditions of release in the receptor. Several methods for wastewater treatment have been reported in the literature, but many of them are high cost and low efficiency. The adsorption process has been used as effective for removal of metal ions. This paper presents studies to evaluate the potential of perlite as an adsorbent for removing metals in model solution. Perlite, in its natural form (NP) and expanded (EP), was characterized by X-ray fluorescence, X-ray diffraction, surface area analysis using nitrogen adsorption (BET method), scanning electron microscopy and Fourier transform infrared spectroscopy. The physical characteristic and chemical composition of the material presented were appropriate for the study of adsorption. Adsorption experiments by the method of finite bath for model solutions of metal ions Cr3+, Cu2+, Mn2+ and Ni2+ were carried out in order to study the effect of pH, mass of the adsorbent and the contact time on removal of ions in solution. The results showed that perlite has good adsorption capacity. The NP has higher adsorption capacity (mg g-1) than the EP. According to the values of the constant of Langmuir qm (mg g-1), the maximum capacity of the monolayer was obtained and in terms of proportion of mass, we found the following order experimental adsorption: Cr3+ (2.194 mg g- 1) > Ni2+ (0.585 mg g-1) > Mn2+ (0.515 mg g-1) > Cu2+ (0.513 mg g-1) and Cr3+ (1.934 mg g-1)> Ni2+ (0.514 mg g-1) > Cu2+ (0.421 mg g-1) > Mn2+ (0.364 mg g-1) on the NP and EP, respectively. The experimental data were best fitted the Langmuir model compared to Freundlich for Cu2+, Mn2+ and Ni2+. However, for the Cr3+, both models fit the experimental data